ASSESSMENT OF AQUIFER PROTECTIVE CAPACITY AND SOIL CORROSIVITY IN UMUNEDE, DELTA STATE, USING DEPTH PROBING RESISTIVITY INVERSION - Akpoyibo, Ogheneovo (FUDMA Journal of Sciences, 2025)
The protective potential and soil corrosivity of the Umunede village in Ika North East, Delta State, was assessed and the study area has been categorized recently among the oil producing towns in the distinct Niger Delta. Ten (10) Vertical Electric Soundings (VES) were sounded and the areas with low or poor (< 0.1 mho), range of moderate (0.2-0.69 mho) and also good (0.7-4.9 mho) protective capacities were identified by evaluating and ascertaining the area's longitudinal conductance. Aquifers in most areas are shielded (prevented) from oil spills in the event of pollution, according to the study, which rates the protective ability (capacity) of the majority of the just discovered oil community as good and moderate. Conversely, areas with identified weak or poor protection capability (capacity) are vulnerable to groundwater taint (contamination) from observed surface spills and also from other nearby sources. VES data indicates soil corrosivity levels, with mild to moderate corrosivity risking pipeline failure. Environmental management initiatives are needed for storm-proofing and protecting the community's aquifer system. This study simplifies the location and distribution of subsurface aquifers, aiding in exploration projects planning for groundwater-producing wells in the study region.
Keywords: Aquifer; Assessment; Corrosivity; Resistivity; Vertical electrical sounding (VES)